VERTEBRATES OF THE MARÍLIA FORMATION (LATE MAASTRICHTIAN) FROM THE PEIRÓPOLIS PALEONTOLOGICAL SITE: TOWARD A BETTER UNDERSTANDING - A. Candeiro Carlos Roberto (Earth Sciences Research Journal)
The Peirópolis paleontological site (Late Cretaceous, Maastrichtian) in Minas Gerais State, Brazil yielded an important assemblage of fossil vertebrates. The typical occurrence of South American widespread taxa in Peirópolis is important for correlation between the Brazilian Bauru Basin and Argentinean Late Cretaceous basins. The fishes, turtles, anuran, crocodilians and dinosaurs known from Peirópolis (Marília Formation) resemble the Patagonian latest Late Cretaceous vertebrate faunas but lacks ornithischian dinosaurs.